Expression-based drug screening of neural progenitor cells from individuals with schizophrenia. Issue 1 (December 2018) - Readhead, Benjamin; Hartley, Brigham; Eastwood, Brian; Collier, David; Evans, David; Farias, Richard; He, Ching; Hoffman, Gabriel; Sklar, Pamela; Dudley, Joel; Schadt, Eric; Savić, Radoslav; et al.
Abstract A lack of biologically relevant screening models hinders the discovery of better treatments for schizophrenia (SZ) and other neuropsychiatric disorders. Here we compare the transcriptional responses of 8 commonly used cancer cell lines (CCLs) directly with that of human induced pluripotent stem cell (hiPSC)-derived neural progenitor cells (NPCs) from 12 individuals with SZ and 12 controls across 135 drugs, generating 4320 unique drug-response transcriptional signatures. We identify those drugs that reverse post-mortem SZ-associated transcriptomic signatures, several of which also differentially regulate neuropsychiatric disease-associated genes in a cell type (hiPSC NPC vs. CCL) and/or a diagnosis (SZ vs. control)-dependent manner. Overall, we describe a proof-of-concept application of transcriptomic drug screening to hiPSC-based models, demonstrating that the drug-induced gene expression differences observed with patient-derived hiPSC NPCs are enriched for SZ biology, thereby revealing a major advantage of incorporating cell type and patient-specific platforms in drug discovery. Unbiased large scale screening of small molecules for drug discovery in psychiatric disease is technically challenging and financially costly. Here, Readhead and colleagues integrate in silico and in vitro approaches to design and conduct transcriptomic drug screening in schizophrenia patient-derived neural cells, in order to survey novel pathologies and points of intervention.